2016
DOI: 10.1016/j.cellsig.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HuR downstream of p38 MAPK promotes cardiomyocyte hypertrophy

Abstract: The RNA binding protein Human antigen R (HuR) interacts with specific AU-rich domains in target mRNAs and is highly expressed in many cell types, including cardiomyocytes. However, the role of HuR in cardiac physiology is largely unknown. Our results show that HuR undergoes cytoplasmic translocation, indicative of its activation, in hypertrophic cardiac myocytes. Specifically, HuR cytoplasmic translocation is significantly increased in NRVMs (neonatal rat ventricular myocytes) following treatment with phenylep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
5
36
1
Order By: Relevance
“…Because PKC is not involved in AVP release induced by ANGII, it is reasonable to suggest that the activation of p38 MAPK can be PKC independent. Indeed, recent studies have reported PKC-independent p38 MAPK activation in some tissues (Lemonnier et al 2004, Samuvel et al 2005, Slone et al 2016. Moreover, we observed that E2 prevented the ANGII-induced p38 MAPK phosphorylation in the PVN and the SON, which can explain the inhibitory effect of E2 on ANGII-induced OT and AVP secretion.…”
Section: Figuresupporting
confidence: 69%
“…Because PKC is not involved in AVP release induced by ANGII, it is reasonable to suggest that the activation of p38 MAPK can be PKC independent. Indeed, recent studies have reported PKC-independent p38 MAPK activation in some tissues (Lemonnier et al 2004, Samuvel et al 2005, Slone et al 2016. Moreover, we observed that E2 prevented the ANGII-induced p38 MAPK phosphorylation in the PVN and the SON, which can explain the inhibitory effect of E2 on ANGII-induced OT and AVP secretion.…”
Section: Figuresupporting
confidence: 69%
“…While relatively little is known about the role of HuR in the myocardium, RNA binding proteins such as HuR are becoming recognized as potentially central regulators of cardiac physiology and pathology (6,7). We have recently shown that HuR is both necessary and sufficient for hypertrophic growth in cultured primary rat myocytes in response to hypertrophic stimuli in vitro (8).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, HuR was previously reported to promote translation of target mRNAs by interacting with IRES sequences located in the 59 UTR (94,95). Moreover, HuR can be activated by p38 MAPK to stabilize target mRNAs (56,(96)(97)(98) and in this context, Farooq et al (56) showed that HuR is required for the survival motor neuron protein increase seen in celecoxib-treated NT2 cells. In our work, we observed that celecoxib induced a marked ;2and 4-fold increase in HuR protein levels in TA and DIA muscles, respectively (Supplemental Fig.…”
Section: Celecoxib Treatment Stimulates Utrophin a Expression In Skelmentioning
confidence: 97%